Limites e potencialidades da participação estudantil em experiências de Radioescola em Fortaleza - Gomes, Luana Amorim (2013)
This dissertation seeks to question the potential of radio schools from the point of view of the student’s participation. Considering the specificities of everyday school, its established rules and the educational guidelines historically constructed, aims to understand whether and how students involved in radio school activities of two elementary schools in the city of Fortaleza- Brazil, under the Brazilian Federal Program called “Mais Educação”, participate in the programs’ production and the conducting of activities related to radio, for example, the choice of topics, research conducting, finalizing the script, choice of music and program implementation, including handling equipments. Accordingly, we seek to identify whether the radio productions have been able to translate the interest of these students, addressing issues related to their daily lives and establish itself as a space which favors the development of their autonomy as subjects. In order to develop this analysis, we rely on authors such as Foucault, Freire, Soares, Souza, among others and we resorted to the methodology used which was the participant observation with ethnographic incursions. Conversations with students participating in the activities of the radios of both schools investigated were also conducted throughout. Based on the research we can conclude that, despite the potential participation of radio school experiences, its existence in the school itself does not ensure the development of autonomous and participatory practices. Making the radio equipment, the computer, the internet access and other more sophisticated equipment available, whereas important, are insufficient to guarantee them. In this perspective, beyond the process of continuous teachers’ training, it is essential to promote the questioning of authoritarian educational models and encourage open dialogue between teachers and students. The radio school can contribute to this process, but it will only do so if mediation of monitors and / or teachers is guided by this commitment.